An antibody to IL-1 receptor 7 protects mice from LPS-induced tissue and systemic inflammation - Jiang, Liqiong; Lunding, Lars P.; Webber, William S.; Beckmann, Karsten; Azam, Tania; Falkesgaard Højen, Jesper; Amo-Aparicio, Jesus; Dinarello, Alberto; Nguyen, Tom T.; Pessara, Ulrich; Parera, Daniel; Orlicky, David J.; et al. (Frontiers in Immunology, 2024)
Interleukin-18 (IL-18), a pro-inflammatory cytokine belonging to the IL-1 Family, is a key mediator of autoinflammatory diseases associated with the development of macrophage activation syndrome (MAS). High levels of IL-18 correlate with MAS and COVID-19 severity and mortality, particularly in COVID-19 patients with MAS. As an inflammation inducer, IL-18 binds its receptor IL-1 Receptor 5 (IL-1R5), leading to the recruitment of the co-receptor, IL-1 Receptor 7 (IL-1R7). This heterotrimeric complex subsequently initiates downstream signaling, resulting in local and systemic inflammation. We reported earlier the development of a novel humanized monoclonal anti-human IL-1R7 antibody which specifically blocks the activity of human IL-18 and its inflammatory signaling in human cell and whole blood cultures. In the current study, we further explored the strategy of blocking IL-1R7 in hyperinflammation in vivo using animal models.We first identified an anti-mouse IL-1R7 antibody that significantly suppressed mouse IL-18 and lipopolysaccharide (LPS)-induced IFNg production in mouse splenocyte and peritoneal cell cultures. When applied in vivo, the antibody reduced Propionibacterium acnes and LPS-induced liver injury and protected mice from tissue and systemic hyperinflammation. Importantly, anti-IL-1R7 significantly inhibited plasma, liver cell and spleen cell IFNg production. Also, anti-IL-1R7 downregulated plasma TNFa, IL-6, IL-1b, MIP-2 production and the production of the liver enzyme ALT. In parallel, anti-IL-1R7 suppressed LPS-induced inflammatory cell infiltration in lungs and inhibited the subsequent IFNg production and inflammation in mice when assessed using an acute lung injury model. Altogether, our data suggest that blocking IL-1R7 represents a potential therapeutic strategy to specifically modulate IL-18-mediated hyperinflammation, warranting further investigation of its clinical application in treating IL-18-mediated diseases, including MAS and COVID-19.